Highly sensitive detection of cobalt through fluorescence changes in β-cyclodextrin-bimane complexes. Issue 81 (11th September 2020) - Pramanik, Apurba; Amer, Sara; Grynszpan, Flavio; Levine, Mindy
Abstract : Cobalt detection is accomplished via efficient fluorescence quenching of a bimane-β-cyclodextrin complex, both in solution and in the solid state. Abstract : A supramolecular complex of syn -(methyl, methyl)bimane (1 ) and β-cyclodextrin demonstrates a sensitive (limit of detection = 0.60 nM) and selective fluorescence turn-off response in the presence of cobalt in aqueous media, with calibration curves enabling quantitation in solution and using filter papers on which bimane and cyclodextrin were adsorbed. 1 H NMR spectroscopy provides insight into interactions underlying the sensor performance.